ANALISIS BIAYA DAN PENDAPATAN PENGOLAHAN GONDORUKEM DAN TERPENTIN DI BEBERAPA PABRIK DI JAWA TENGAH - Sylviani Sylviani; Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1989)
Collophonium     industrial   development     in  Central  Java  serves   two  purposes,    i.e,  a  new  source   of   income,   and improving   the product  efficiency   for Perhutani   state  forest  enterprise.Based   on  research  results   on  four   collophonium     industries,    the  production  costs   ranging  from   Rp   109.37   ta Rp.  140. 70 with an average of Rp  127.46/kg  with  10%  coefficient of variation.  The production costs  elements  consisting  of manufacturing    cost   (Rp   120.28/kg)     representief   94%  of  the  total  costs  and  Rp   7.18/kg    for  administrative   cost.   The average Profit   before   tax  for  the  mill  run  by  Perhutani   was found   to  be  Rp  40.12/kg,    while  those  run  by  the private sector  was as high  as Rp  44.66/kg.